Origin of Nitric Oxide Reduction Activity in Flavo–Diiron NO Reductase: Key Roles of the Second Coordination Sphere. (14th February 2019) - Lu, Jiarui; Bi, Bo; Lai, Wenzhen; Chen, Hui
Abstract: The second coordination sphere constitutes a distinguishing factor in the active site to modulate enzymatic reactivity. To unravel the origin of NO‐to‐N2 O reduction activity of non‐heme diiron enzymes, herein we report a strong second‐coordination‐sphere interaction between a conserved Tyr197 and the key iron–nitrosyl intermediate of Tm FDP (flavo–diiron protein), which leads to decreased reaction barriers towards N–N formation and N–O cleavage in NO reduction. This finding supports the direct coupling of diiron dinitrosyl as the N–N formation mode in our QM/MM modeling, and reconciles the mechanistic controversy of external reduction between FDPs and synthetic biomimetics of the iron–nitrosyls. This work highlights the application of QM/MM 57 Fe Mössbauer modeling in elucidating the structural features of not only first, but also second coordination spheres of the key transient species involved in NO/O2 activation by non‐heme diiron enzymes. Abstract : Eine zweite Chance : QM/MM‐Simulationen zeigen, dass die Aktivität von Flavodieisen‐NO‐Reduktase durch den Effekt einer zweiten Koordinationssphäre, der seine Ursache in einem Tyrosinrest hat, deutlich erhöht werden kann. Die Erkenntnisse helfen dabei, den mechanistischen Ursprung der NO‐Reduktase‐Aktivität in Flavodieisen‐Proteinen zu entschlüsseln.